In the method of international programming of teachers in professional education development of pedagogical skills in the formation of competition - Nurimbetov Akhmadjan Niyazmbetovich; Mambetova Sayyora Madraimovna (Zien Journals, 2022)
This article talks about the current work of the pedagogue and the development of the competencies noted in the standards of international evaluation programs. about the opportunities presented by him
Keywords: professional education; pedagogical competence; pedagogical skills; educational aspects